Indexicality in EFL Classroom Learning: A Critical Classroom Discourse Analysis - Fajar, Muh; Intakha, Alaudy Hendy; Sulistyowati, Heny (Journal of English Teaching and Learning Issues, 2025)
This study examined dialogues between a lecturer and his students in an EFL classroom learning to find out indexicality. It employed a qualitative technique. The data were dialogues by the lecturer and his students at English Department of the higher education institution in Jombang when they were involved the learning process of the Classroom Discourse class. There were two instruments in this study, they were the researcher himself and documentation. In terms of indexicality, the participants used personal deixis o strengthen his position on the issues faced by the lecturer when the utterance is addressed and forces the audience to accept his views. In addition, the shift in deixis "I" to "We" throughout the classroom learning interaction could also be an attempt to ensure that students were persuaded. The use of the sign "We" which is predominantly indexical by the lecturer convinces students to believe that the learning delivered in class is a collective statement and not a personal statement. Furthermore, the lecturer employed politeness to keep his relationship with his students well. Thus, it could be concluded that indexicality in this study had two kinds of relations, they were equal and unequal relations. Equal relations were represented using positive deixis and positive politeness, whereas unequal relations were represented by negative deixis and negative politeness.